Extent of Functional Immunity Granted to State Officials - Tiwari, Ayush (Christ University Law Journal, 2019)
Being a part of the international community has greatly altered the relations between different states. This article will focus on the concept of diplomatic immunity, and, specifically, functional immunity provided to state officials in the realm of international law. A thorough insight into the Vienna Convention regarding Diplomatic Immunity has furthered the scope of present research. Furthermore, a line of distinction is drawn between personal and functional Immunity. This paper will also take a look into the assumptions relating to functional immunity within international law and also evaluate its doctrinal approaches. Additionally, the legal ambit of the official Act, the importance for states to recognize functional immunity is also discussed. This article will not only talk about provisions established in law but also the customs which are adopted in relation to the functioning of rationemateriae. The possibility of weighing functional immunity alongside the states’ civil and criminal jurisdiction is also evaluated in the concluding part.